Peer Community Journal 2021
DOI: 10.24072/pcjournal.54
|View full text |Cite
|
Sign up to set email alerts
|

Intra and inter-annual climatic conditions have stronger effect than grazing intensity on root growth of permanent grasslands

Abstract: Intra and inter-annual climatic conditions have stronger effect thangrazing intensity on root growth of permanent grasslands, Peer Community Journal, 1: e43.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…The absence of any effect of stocking intensity on SOC stocks is in accordance with previous studies (Herfurth et al, 2016; Picon‐Cochard et al, 2021; Wright et al, 2004). For instance, Herfurth et al (2016) found no differences after 7 years of varied grazing intensity on SOC stocks.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of any effect of stocking intensity on SOC stocks is in accordance with previous studies (Herfurth et al, 2016; Picon‐Cochard et al, 2021; Wright et al, 2004). For instance, Herfurth et al (2016) found no differences after 7 years of varied grazing intensity on SOC stocks.…”
Section: Discussionsupporting
confidence: 92%
“…López‐Mársico et al (2015) found increased BGB in grazed sites compared to ungrazed exclusion zones, while Picon‐Cochard et al (2021) found no differences but a large interannual variation of roots. Tall patches are basically comparable to grazing exclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation